2022
DOI: 10.21037/atm-22-479
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of a novel ferroptosis-related gene model in breast cancer

Abstract: Background: Breast cancer (BRCA) is the most common malignancy with high heterogeneity in women, and the prognostic prediction for BRCA has remained poor. Ferroptosis, a recently identified iron-dependent form of programmed cell death, plays a significant role in BRCA treatment. Some BRCA cell lines are proven to be sensitive to ferroptosis, and some ferroptosis-related genes have been identified as divers or suppressors in the progress of BRCA. This study aimed to explore the prognostic value of ferroptosis-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…To further explore the predictive ability of our signature, a comparison was performed among several significant molecular signatures employed for predicting OS in patients with BC. Compared with the other signature, such as ferroptosis, necroptosis, pyroptosis, and immune-related ( Lin et al, 2020 ; Zhong et al, 2020 ; Wang et al, 2021a ; Wu et al, 2021a ; Zhu et al, 2021b ; Ding et al, 2021 ; Ye et al, 2021 ; Lu et al, 2022a ; Lu et al, 2022b ; Chen et al, 2022 ; Chu et al, 2022 ; Yu et al, 2022 ; Zou et al, 2022 ), our signature indicated much higher AUCs, which indicated a better predictive ability, especially in predicting the long-term survival status. Furthermore, we constructed a prognostic nomogram that could simplify treatment decision-making for patients with BC.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…To further explore the predictive ability of our signature, a comparison was performed among several significant molecular signatures employed for predicting OS in patients with BC. Compared with the other signature, such as ferroptosis, necroptosis, pyroptosis, and immune-related ( Lin et al, 2020 ; Zhong et al, 2020 ; Wang et al, 2021a ; Wu et al, 2021a ; Zhu et al, 2021b ; Ding et al, 2021 ; Ye et al, 2021 ; Lu et al, 2022a ; Lu et al, 2022b ; Chen et al, 2022 ; Chu et al, 2022 ; Yu et al, 2022 ; Zou et al, 2022 ), our signature indicated much higher AUCs, which indicated a better predictive ability, especially in predicting the long-term survival status. Furthermore, we constructed a prognostic nomogram that could simplify treatment decision-making for patients with BC.…”
Section: Discussionmentioning
confidence: 78%
“…In our study, the AUCs of the signatures at 3-, 5-, and 10-year were 0.683, 0.640, and 0.794, respectively, significantly higher than most hallmark predictive models. Table 1 showed that the 3-, 5-, and 10-year AUCs of the other four prognostic signatures, namely, the 9 ferroptosis-related gene signature (3-, 5-, and 10-year AUCs: 0.713, 0.713, and 0.684) ( Lu et al, 2022a ), 4 immune-related gene signature (3-, 5-, and 10-year AUCs: 0.692, 0.691, and 0.715) ( Ding et al, 2021 ), 7 pyroptosis-related gene signature (3-, 5-, and 10-year AUCs: 0.785, 0.769, and 0.711) ( Chu et al, 2022 ), and 6 autophagy-related gene signature (3-, 5-, and 10-year AUCs: 0.640, 0.600, and 0.610) ( Zhong et al, 2020 ) were comparable to the predictive capabilities of our predictive model, and our signature stand out with a clear advantage in predicting the long-term survival of BC patients, with a 10-year AUC of 0.819. We also listed the other signatures that focus more on short-term survival, such as 1-year, 2-year, 3-year, and 5-year survival.…”
Section: Resultsmentioning
confidence: 99%
“…The ferroptosis-related gene signature has been successfully constructed to predict the prognosis in patients with hepatocellular carcinoma [ 56 ], breast cancer [ 57 ], pancreatic adenocarcinoma [ 58 ], and cholangiocarcinoma [ 59 ]. Additionally, in LUAD, a ferroptosis-related gene signature including five genes was constructed to predict prognosis [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“… 5 Studies have shown that some ferroptosis-related genes have been identified as suppressor genes in the process of BRCA. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…5 Studies have shown that some ferroptosisrelated genes have been identified as suppressor genes in the process of BRCA. 6,7 CISD1 is a protein containing the CDGSH iron-sulfur domain, which is located in the outer membrane of mitochondria and is known to negatively regulate ferroptosis. 8 While studies have found that CISD1 plays an important role in promoting tumorigenesis and tumor progression in many cancer types, 9 recent studies also suggest that CISD1 can be used as a biomarker and target for breast cancer.…”
Section: Introductionmentioning
confidence: 99%